The Missionary Activity of the Pope Gregory the Great - Dawid Dudziak (Wrocławski Przegląd Teologiczny)
The Migration Period at the turn of antiquity and the Middle Ages changed the face of Europe permanently. The Fall of the Roman Empire in the West showed that the functioning of the state and church administration must change. This was perfectly understood by Pope Gregory the Great, who, understanding the circumstances, undertook the task of re-evangelising Europe. In this undertaking, the monks played a significant role as missionaries of the new Europe. The Pope restored to the Holy See the priority in organizing missions and evangelization, which had been the domain of the secular power of the Empire for several centuries. Gregory the Great left behind numerous guidelines and advice for the missionaries, and he personally ensured that everyone entrusted with the task of evangelization was properly prepared for it. As the basis of the mission, Gregory considered, first and foremost, the testimony of the life of missionaries according to the so-called spirituality exemplum. In addition to the proclamation of the Gospel, monks were required to be active witnesses of love, demonstrated by the establishment of structures for the service of caritas. In his decisions, the Pope was firm and courageous, which is why posterity gave him the title of First European.